Factor analysis of nurses’ satisfaction with educational installation training in hospitals: A cross-sectional study - Nur Akli; Ali Harokan; Gema Asiani (Lentera Perawat, 2025)
Background: Nurse job satisfaction plays an essential role in improving the quality of nursing care and patient safety. Several factors, including leadership, work environment, promotion opportunities, training, educational installation activities, and work tenure, have been shown to influence nurses’ satisfaction. Objective: This study aimed to analyze factors associated with nurses’ satisfaction regarding educational installation training in hospitals. Methods: This research applied a quantitative cross-sectional design. The study population comprised 90 inpatient nurses at  dr. AK Gani Hospital Palembang, selected through total sampling. Data were collected using a validated and reliable structured questionnaire. Data analysis employed chi-square tests for bivariate analysis and multiple logistic regression for multivariate analysis with a 95% confidence level. Results: Bivariate analysis revealed significant factors including work tenure (p=0.000; OR=0.093), leadership (p=0.001; OR=4.984), work environment (p=0.003; OR=4.054), promotion opportunities (p=0.034; OR=2.737), training (p=0.007; OR=3.575), and educational installation activities (p=0.002; OR=4.516). Multivariate analysis identified work tenure as the most dominant factor (OR=412.585), followed by educational installation activities (OR=57.295), training (OR=27.712), work environment (OR=28.014), promotion opportunities (OR=24.429), and leadership (OR=19.420). Conclusion: Nurse satisfaction is significantly influenced by organizational factors and work experience, with work tenure serving as the strongest predictor. Hospitals should strengthen leadership, create supportive work environments, ensure fair promotion opportunities, and provide continuous training and educational installation activities to enhance nurse job satisfaction.